Contribution of North Sami everyday Christianity to a cosmologically-oriented Christian theology - Johnsen, Tore (The University of Edinburgh, 2020)
The thesis explores the question of the contribution of North Sami everyday Christianity to cosmologically-oriented Christian theology. The basic assumption underpinning the study is that a ‘cosmological orientation’ – that is, the way people enact and perceive their participation in the world – constitutes a deeply theological matter closely associated with their worldview. I argue that such worldview assumptions are not entirely given within the Christian faith itself but depending in part on the basic religio-philosophical dialogue partners informing a theological tradition. The study explores the cosmological orientation of Christian theology by privileging the tradition of North Sami everyday Christianity. The Sami are the indigenous people of Sápmi, a vast region in today’s northern Norway, Sweden, Finland, and north-west Russia. Despite the colonial ways in which Christianity was introduced, the North Sami developed a Christian culture informed by indigenous ways of relating to the world. The material core of the study is based on a qualitative insider’s study of lived religion among North Sami everyday Christianity in four municipalities in Finnmark, Norway. Twenty-eight research participants of reindeer herding, settled inland / river Sami, and sea Sami backgrounds are interviewed in depth about the spiritual traditions they grew up with, and how they reflect on these today. The dominant overarching cosmological orientation coming out of the qualitative study (Chapters 4-5) is captured in the phrase ‘nature-centered Ipmiláhčči-faith’ (God the Father-faith). The overarching discussion is supported by diachronic analysis; that is, a critical deconstruction of historic Lutheran theological discourses on the Sami tradition from the Lutheran Reformation onwards (Chapter 3). The cosmological orientation of North Sami everyday Christianity is unpacked and theologically engaged through the lens of African and Native American theologies (Chapter 6). Its intersections with contemporary Norwegian Lutheranism is ...